Risks and Returns : Managing Financial Trade-Offs for Inclusive Growth in Europe and Central Asia - Gould, David Michael (Washington, DC: World Bank, 2016)
During the 1990s, Emerging Europe and Central Asia (ECA) chose a model of rapid financial development emphasizing bank credit expansion often funded by foreign capital. Although boosting financial inclusion of firms and households, the model was accompanied by lower efficiency and increased financial vulnerability. After two waves of crises, in the late 1990s and after 2008, ECA’s banking systems again face major stress. The crises and stresses have eroded trust in banks and job creation in credit-dependent firms. ECA’s shallow and illiquid capital markets offer no additional support. Stagnating income growth, particularly of middle- to lower-income earners, has led to increasing dissatisfaction with low productivity growth and limited opportunities. This frustration provides the impetus for reshaping financial policies. A healthy and balanced financial sector could strengthen structural adjustment in ECA’s eastern, oil-dependent economies and innovation in its western countries.